A chronic oral reference dose for hexavalent chromium‐induced intestinal cancer†. Issue 5 (14th August 2013) - Thompson, Chad M.; Kirman, Christopher R.; Proctor, Deborah M.; Haws, Laurie C.; Suh, Mina; Hays, Sean M.; Hixon, J. Gregory; Harris, Mark A.
ABSTRACT High concentrations of hexavalent chromium [Cr(VI)] in drinking water induce villous cytotoxicity and compensatory crypt hyperplasia in the small intestines of mice (but not rats). Lifetime exposure to such cytotoxic concentrations increases intestinal neoplasms in mice, suggesting that the mode of action for Cr(VI)‐induced intestinal tumors involves chronic wounding and compensatory cell proliferation of the intestine. Therefore, we developed a chronic oral reference dose (RfD) designed to be protective of intestinal damage and thus intestinal cancer. A physiologically based pharmacokinetic model for chromium in mice was used to estimate the amount of Cr(VI) entering each intestinal tissue section (duodenum, jejunum and ileum) from the lumen per day (normalized to intestinal tissue weight). These internal dose metrics, together with corresponding incidences for diffuse hyperplasia, were used to derive points of departure using benchmark dose modeling and constrained nonlinear regression. Both modeling techniques resulted in similar points of departure, which were subsequently converted to human equivalent doses using a human physiologically based pharmacokinetic model. Applying appropriate uncertainty factors, an RfD of 0.006 mg kg–1 day–1 was derived for diffuse hyperplasia—an effect that precedes tumor formation. This RfD is protective of both noncancer and cancer effects in the small intestine and corresponds to a safe drinking water equivalent level of 210 µg l–1. This concentration is higher than the current federal maximum contaminant level for total Cr (100 µg l–1) and well above levels of Cr(VI) in US drinking water supplies (typically ≤ 5 µg l–1). © 2013 The Authors. Journal of Applied Toxicology published by John Wiley & Sons, Ltd.